Safety culture in surgical centers from the perspective of the multiprofessional team - Nery José de Oliveira Junior; Daniela Campos de Andrade Lourenção; Vanessa de Brito Poveda; Caren de Oliveira Riboldi; Fabiana Zerbieri Martins; Ana Maria Müller de Magalhães (Universidade Federal do Ceará, 2022)
Objective: to evaluate the safety culture through an observation of the safety climate of health workers from a Surgical Center. Methods: cross-sectional study in eight surgical centers from a hospital complex. A validated Brazilian version of the Safety Attitudes Questionnaire/Operating Room was applied to a convenience sample of 172 health and support workers (physicians and nurses). The Chi-squared, Student's t, and Mann-Whitney's tests were used. Results: the general evaluation showed a positive safety climate. Only the nursing professionals reached the minimum score that indicates a positive result in the domain Quality of communication and collaboration. The domains Safety climate, Stress recognition, Communication in the surgical environment, and Perception of professional performance showed positive results, while Perception of management and Work conditions had the worst scores. Conclusion: the safety climate was positive. Nonetheless, communication showed shortcomings pointed out by the workers. Contributions to practice: identifying domains that need to be improved helps fomenting safety culture in surgical centers, leading to better care outcomes and work environments.